Stressors and coping strategies among Baccalaureus technologiae undergraduate nursing students at a Western Cape higher education institution - Rossouw, Freda Marina (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCur)--Stellenbosch University, 2018.